Chlorido(2-{1- (2-morpholinoethyl)imino ethyl}phenolato-kappa N-3,N ',O)copper(II) - Hisham, N.A.I.; Ali, Hapipah Mohd; Khaledi, H.; Gwaram, N.S. (International Union of Crystallography, 2011)
In the title compound, [CuCl(C14H19N2O2)], the Cu-II ion is four-coordinated by one deprotonated N,N',O-tridentate Schiff base and one chloride ion in a distorted square-planar geometry. In the crystal, adjacent molecules are linked via C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions, forming infinite layers parallel to the (100) plane. The structure was determined from a non-merohedrally twined crystal [twin ratio 0.777 (3):0.223 (3)].